2017
DOI: 10.1002/1873-3468.12689
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of HNF1α in hepatocytes results in fatty liver‐related hepatocellular carcinoma in mice

Abstract: Hepatocyte nuclear factor 1α (HNF1α) is a liver-enriched transcription factor that is critical for the maintenance of hepatocyte function. Our previous studies have demonstrated the therapeutic effects of HNF1α on hepatic fibrosis and hepatocellular carcinoma (HCC) in animals. In this study, we created hepatocyte-specific Hnf1α knockout mice using the Cre-loxP recombination system. The knockout mice display increased fatty acid synthesis in the liver. Moreover, these mice spontaneously develop HCC through fatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 43 publications
(50 reference statements)
2
24
0
Order By: Relevance
“…It has been shown that the expression of HFN‐1α is associated with cancer risk in several tumors, including hepatocellular and pancreatic carcinoma, renal cancer, ovarian cancer, endometrial cancer, and prostate cancer . However, recent studies also reported the antitumor potentials of HFN‐1α . At this juncture, it is not clear whether the downregulation of HFN‐1α observed in this study is responsible for apoptosis induction and hence, further studies are warranted on these lines.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…It has been shown that the expression of HFN‐1α is associated with cancer risk in several tumors, including hepatocellular and pancreatic carcinoma, renal cancer, ovarian cancer, endometrial cancer, and prostate cancer . However, recent studies also reported the antitumor potentials of HFN‐1α . At this juncture, it is not clear whether the downregulation of HFN‐1α observed in this study is responsible for apoptosis induction and hence, further studies are warranted on these lines.…”
Section: Discussionmentioning
confidence: 65%
“…29,30 However, recent studies also reported the antitumor potentials of HFN-1α. 31,32 At this juncture, it is not clear whether the downregulation of HFN-1α observed in this study is responsible for apoptosis induction and hence, further studies are warranted on these lines.…”
Section: Discussionmentioning
confidence: 87%
“…We have previously reported that the enforced expression of HNF1α impedes the growth of HCC xenografts in mice by inducing the differentiation of hepatoma cells into hepatocytes [ 9 ]. Our recent study further demonstrated that hepatocyte-specific Hnf1α knockout mice spontaneously develop HCC from fatty liver without cirrhosis [ 10 ]. In addition, it has been reported that HNF1α inhibits Wnt and NF-κB signalling during hepatocarcinogenesis and HCC metastasis by transcriptionally regulating the expression of miR-194 [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The probably mechanism of it on insulin level and lipometabolic disorder might be related to targeted tissues of insulin, i.e., liver and surrounding adipose. HNF1α and CTRP6 are supposed to be the substance metabolic indicators of these two targets during lowering lipid (32, 33). Deficiency of HNF1α in liver lipometabolism may lead to diabetes and hypercholesterolemia by increasing bile acid and cholesterol synthesis (34, 35).…”
Section: Discussionmentioning
confidence: 99%